Structural basis of chromatin regulation by histone variant H2A.Z. Issue 19 (13th October 2021) - Lewis, Tyler S; Sokolova, Vladyslava; Jung, Harry; Ng, Honkit; Tan, Dongyan
Abstract: The importance of histone variant H2A.Z in transcription regulation has been well established, yet its mechanism-of-action remains enigmatic. Conflicting evidence exists in support of both an activating and a repressive role of H2A.Z in transcription. Here we report cryo-electron microscopy (cryo-EM) structures of nucleosomes and chromatin fibers containing H2A.Z and those containing canonical H2A. The structures show that H2A.Z incorporation results in substantial structural changes in both nucleosome and chromatin fiber. While H2A.Z increases the mobility of DNA terminus in nucleosomes, it simultaneously enables nucleosome arrays to form a more regular and condensed chromatin fiber. We also demonstrated that H2A.Z's ability to enhance nucleosomal DNA mobility is largely attributed to its characteristic shorter C-terminus. Our study provides the structural basis for H2A.Z-mediated chromatin regulation, showing that the increase flexibility of the DNA termini in H2A.Z nucleosomes is central to its dual-functions in chromatin regulation and in transcription.